Subcritical approximations to stochastic defocusing mass-critical nonlinear Schrödinger equation on R - Fan, C; Xu, W (Elsevier, 2019)
We show robustness of various truncated and subcritical approximations to the stochastic defocusing mass-critical nonlinear Schrödinger equation (NLS) in dimension d=1, whose solution was constructed in [8] with one particular such approximation. The key ingredient in the proof is a uniform bound of the solutions to the family of deterministic mass-subcritical defocusing NLS.